Doctrine of condonation: challenges in the management of disciplinary cases in public university - Romli, Fariza; Md Dahlan, Nuarrual Hilal; Ahmad, Rusniah (UUM College of Law, Government and International Studies, 2016)
The disciplinary committee in public university carry a huge responsibilities to uphold justice to the employer as well as to the employee in handling the disciplinary cases.One of the hindrance faced by the committee is the issue on doctrine of condonation as a waiver.Thus, it is important to understand what is doctrine of condonation in order to identify, prevent, control and deal with it when used as a defense by the employee to prevent him from being punished by the authorities. Therefore, this paper will examine the definition of the doctrine of condonation, explain the protection under Statutory Bodies (Discipline and Surcharge) Act 2000 [Act 605] with regards to condonation, identifies the elements of a waiver by looking at the application of the doctrine by the court and the implications of the doctrine as a challenge in disciplinary cases in public universities. The methodology used is based on library research with an analysis of the legal acts, regulations and case law.The author found that the disciplinary action should be done effectively by the authorities to make sure that action is taken within reasonable time. Lack of certain rules or procedure can cause detriment in handling the issues on condonation.